Meta-analysis about correlation between the human Papillomavirus infection and the incidence of cervical intraepithelial Neoplasia - Mingyang Wang; Xiaofeng Zou; Zhiliang Wang (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the correlations between human papillomavirus infection and the incidence of cervical intraepithelial neoplasia. Method:This study was conducted in the Affiliated Hospital of Zunyi Medical University, Zunyi, China in January 2024. The systematic review and meta-analysis comprised literature search on PubMed, Medline, Embase, Cochrane Library, Web of Science, China Biomedical and Wanfang databases for studies published from January 2010 to December 2020 related to human papillomavirus and cervical intraepithelial neoplasia. The quality of the studies was evaluated using the Newcastle- Ottawa Scale, and meta-analysis was done using RevMan 5.3. Results: Of the 854 studies identified, 10(1.2%) were included; 7(70%) in English and 3(30%) in Chinese. There was a total of 193,000 patients; 94,298(49%) in the observation group and 98,702(51%) in the control group. Human papillomavirus infection was closely correlated with cervical intraepithelial neoplasia-1, cervical intraepithelial neoplasia-2 and cervical intraepithelial neoplasia-3 in women, with odds ratios of 3.94 (95% confidence interval: 3.53-4.40), 1.03 (95% confidence interval: 1.01-1.06) and 1.13 (95% confidence interval: 1.10-1.16), respectively. Both human papillomavirus single infection and reinfection in cervical intraepithelial neoplasia patients were significantly higher than in normal women, with odds ratios of 0.50 (95% confidence interval: 0.41-0.61) and 0.43 (95% confidence interval: 0.35-0.53), respectively. Conclusion: The incidence of cervical intraepithelial neoplasia was found to be highly associated with human papillomavirus infection, and the infection increased the risk of cervical diseases. Keywords: Human papillomavirus, HPV infection, Cervical intraepithelial neoplasia, CIN, Cervical diseases, Meta-analysis.